Law Enforcement Of Corruption Crime Cases In Jayapura (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to analyze the law enforcement of corruption, law enforcement efforts and the factors that influence the law enforcement of corruption in Jayapura. The research method used is normative juridical and empirical juridical research types. The results of this study indicate that: first, the essence of law enforcement on corruption (Studies in Jayapura) in principle is to prevent irregularities or misappropriation of state finances to realize social welfare. However, in practice, it is not optimal because of the minimal application of criminal sanctions against corruption convicts and the lack of oversight of state financial management.